Radzenie sobie ze stresem u rodziców dzieci ze spektrum autyzmu = Coping with stress for parents of children with autism spectrum disorder - Koselska, Anna; Mróz, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The research results presented in this article focus on the differences in stress experiences between parents of children with autism spectrum disorder (N?=?46) and parents of typically developing children (N?=?40). The comparative study considered three variables: the level of experienced stress, coping styles, and positivity level. Additionally, the correlation between stress levels and positive attitudes in parents was examined. Three questionnaires were used in the study: the PSS-10 (Perceived Stress Scale), the CISS (Coping Inventory for Stressful Situations), and the PT (Positivity Test).
Keywords: rodzice dzieci ze spektrum autyzmu; poziom stresu; pozytywne nastawienie; parents of children on the autism spectrum; stress level; positivity level